Empirical analysis of dividend smoothing policy: Evidence from selected Asian emerging markets / Syed Karim Bux Shah - Syed Karim , Bux Shah (2018)
Dividend smoothing is a prominent feature of dividend policy; however, little is known about its causes and its relevance to the value of the firm. While the theory suggests that companies smooth dividend to signal their prospects or to mitigate agency conflicts, the empirical evidence contradicts these predictions, leading to a puzzle: why dividend smoothing is higher among firms which do not need it. Moreover, despite the prevalence of dividend smoothing, an empirical analysis of it from the emerging markets' perspective is non-existent. This study, thus, analyzes dividend smoothing behavior of a large sample of firms from selected Asian emerging markets from 2004 to 2015. The first objective investigates the extent to which firm-level informational asymmetries and agency costs affect the degree of dividend smoothing. Addressing the inconsistencies found in the literature, this study proposes a novel approach that takes reputational effects arising from the firm’s prior tendency towards smoothing into account. The study argues that the firm’s prior tendency toward smoothing establishes its reputation as a high- or low-smoothing firm, which in turn affects the level of dividend smoothing, particularly among the high-smoothing firms. Therefore, the dividend strategy of a high-smoothing firm is objectively different from that of a low-smoothing firm, which requires particular attention. The results based on quantile regression support this hypothesis showing that most of the proxies for information asymmetry and agency cost, which are significant at lower quantiles, turn statistically insignificant at the higher quantiles of dividend smoothing. The fact that reputational factors are dominant in determining the dividend smoothing among high-smoothing firms helps resolve the puzzle of why firms facing lower information asymmetry and agency costs are still high dividend smoothers. The second objective examines the impact of financing constraints on dividend smoothing. Consistent with financing constraints view, constrained firms smooth more compared to unconstrained firms due to their significantly slower rate of increasing dividends. Additional analysis suggests that, unlike in low-smoothing firms, dividend smoothing in high-smoothing firms is insensitive to the variations in financing constraints indicating further support for the dominance of reputational effect. The third objective investigates the impact of the country-level legal and financial structures on dividend smoothing. Supporting the outcome model, the findings indicate that firms smooth dividend more when investors’ rights are better protected. As for financial structure, results show that dividend smoothing is higher in countries with more market-based systems. Finally, under the fourth objective, it is observed that high-smoothing firms have significantly higher Tobin’s Q values than low-smoothing firms, signifying a positive relationship between smoothing and the value of the firm. The study makes several contributions. Empirical analysis of dividend smoothing distinguishing between high- and low-smoothing firms is of particular interest for setting future theoretical directions. Analyzing the impact of financing constraint on dividend smoothing and relationship between smoothing and firm value fills the existing gap in the literature especially from emerging markets perspectives. Finally, the findings on the micro and macro-level determinants of dividend smoothing are expected to assist international investors and portfolio managers in making more efficient asset allocations.